Acquired Childhood Dysarthria Classification - J Gordon Millichap (Pediatric Neurology Briefs, 1998)
Published reports of acquired childhood dysarthria since 1980 were reviewed at University Hospital, Rotterdam; and the Department of Medical Psychology, Ziekenhuis Walcheren, Vlissingen, The Netherlands, and cases were classified on the basis of neuroradiological location of lesion and associated motor disorders.